La titularidad y otras cuestiones sobre el derecho a la vivienda digna y decorosa en México - Salgado Calvillo, Luis Eduardo (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
When we talk about National Infrastructure, we understand that one of the functions of the State is to homogenize the plurality of the cultures that had settled down on it. Furthermore, it has to harmonize all the possible disagreement that might arise as a consequence of their ideology, religion, gender, sexual preference and social condition. The phenomenon of globalization and economic liberalism and free trade, is one of the contributing factor that makes a big gap between social classes in Mexico, having as a result severe poverty and on the other hand extreme richness. In order to give a guarantee the Mexican people social and economic rights, since 1917 the constitution, promised equal opportunity, restoration of the land and dramatic economic reforms, as well as protection of those in need. In light of these new economic and social rights, we have a better understanding of the right to housing. This is recognised in the fourth article and awards the opportunity to adequate housing and shelter. However, the right to housing is not accurate because the holder of this right is the “family” and this term is not explained neither in the Constitution nor the implementing legislation. Despite of the efforts that the Mexican government has done by offering new conditions and terms about the right to housing, unfortunately, it hasn’t been enough. That is the reason I want to contribute with this essay to a new vision of this right. My proposal is based on the study of the history and development of the Spanish right to housing. As a result of the difficulties to apply the right to housing, some people are not able to buy houses. This leads to another problem: shanty towns. In conclusion, the fact that we do not have enough job opportunities and the minimum wage in this country is too low, the standard of living, including housing, is a right that can only be executed by rich people.

Cuando se habla de la organización de un Estado, se sobreentiende que este deberá de involucrar y no pasar por alto la pluralidad de los grupos que en él conviven así como las diferencias que pudieran surgir entre género, preferencia sexual, religión, ideología y condición social. La globalización y las prácticas de libre mercado, han hecho en países en vías de desarrollo como el nuestro que las clases sociales sean muy extremas, existiendo grandes abismos de pobreza y desigualdad. En México la reforma que a la Constitución de 1857, mejor conocida como la Constitución de 1917, implantó por primera vez los derechos sociales con la finalidad de garantizar dicha igualdad económica y el aseguramiento y protección de las clases más desprotegidas. Es entonces, que dentro del artículo cuarto constitucional, el Estado Mexicano tiene la obligación de asignar y distribuir los recursos necesarios para que las personas tengan acceso a una vivienda digna y decorosa, sin embargo, en principio este derecho constitucional plantea una discriminación, puesto que los titulares de este derecho son “toda familia”, y en la constitución o en la ley reglamentaria de vivienda no existe una definición de lo que significa el termino familia. Los programas ofertados por el gobierno mexicano sobre la materia han resultado ser insuficientes, es por ello que a la luz de una estancia de investigación que realice en la ciudad de Sevilla, España, este trabajo pretende aportar la experiencia desarrollada por aquel país. Al no contar con una vivienda, las personas se asientan irregularmente. La falta de oportunidades laborales en el país, y la baja remuneración en los salarios mínimos, hacen pensar que poder contar con una vivienda en México es un lujo.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2016-0302; Procesal constitucional; Obligación del Estado; Desigualdad; Derecho humano; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/710